The Bolt phenomenon - Rowbottom, M. (New Studies in Athletics, 2011)
Usain Holt is the world's highest profile athlete, an international known figure on the scale of any football player or movie star. Through his success in athletics' most popular events, he has almost single-handedly brought the sport to a new generation wherever it is followed, as well as some places where it was not previously strong. His star power has been confirmed with the signing of the largest ever sponsorship deal for a track and field athlete. This article traces Bolt's development, from his birth through to the end of the 2010 season. It chronicles his early career, his decision to become a professional athlete, his lifestyle adjustments and health problems, his emergence in the global sporting consciousness with a world record in the 100m in early 2008, and his phenomenal performances in the 2008 Olympic Games and 2009 IAAF World Championships in Athletics. Along the way the social and sporting background to the strength of Jamaica's sprinters, the role of Bolt's coach and support team and his impact on the whole spart of athletics are covered. The article concludes that Bolt is not bigger than athletics, but he is undeniably the biggest thing in the sport.